The Future of Teacher Education Under NEP 2020: A Review of Key Reforms - M. Sarasija (AG Volumes, 2025)
Teaching is one of the noblest professions, shaping the future of both students and the nation. Teacher education is essential for developing competent educators equipped to meet professional challenges. NEP 2020 introduces transformative reforms to enhance teacher training quality and effectiveness. Key reforms include mandatory Continuing Professional Development (CPD), strengthened accreditation processes, mentorship programs, technology-integrated pedagogies, and digital literacy training. The policy emphasizes research-based practices, inclusive education, diversity training, global exposure, and international collaborations. A shift from knowledge-based to performance-based assessments ensures better competency evaluation. Additionally, government support and policy alignment play a crucial role in effective implementation. This review analyzes various literature on NEP 2020’s vision for teacher education, concluding that these reforms aim to empower educators, improve training standards, and create a more dynamic, inclusive, and globally competitive teaching framework.